The Use of Waste Ceramic Optimal Concrete for a Cleaner and Sustainable Environment - A Case Study of Mechanical Properties - Najm, Hadee Mahommed; Ahmad, Shakeel (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The present study aims to find out the optimal use of ceramic powder and ceramic aggregate (both fine and coarse) as a possible substitute for Ordinary Portland Cement (OPC 43 grade) and natural aggregate (fine and coarse), respectively, in concrete, where focused on investigating the mechanical properties of waste ceramic concrete. The performance of this modified concrete was evaluated in terms of Compressive Strength (CS), Tensile Strength (TS), Flexural Strength (FS), and Combined Flexural and Torsional strength (FTS) obtained based on various experimental tests conducted on a total of 192 samples (48 cubes, 48 cylinders, 96 beams).
Keywords: ceramic waste; concrete; mechanical performance; ceramic floor tiles; strength; odpady ceramiczne; beton; wydajność mechaniczna; płytki podłogowe ceramiczne; wytrzymałość